How Do Organizational Commitment and Workload Influence Cyberloafing Behavior: Case Study of RSJD Nurses in Lampung Province - Julia Epitia; Nova Mardiana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Cyberloafing, or employees engaging in non-work-related internet activities, has become a prevalent issue for many companies. Finding out how organizational commitment and workload affect cyberloafing behavior in nurses at the Lampung Province Regional Mental Hospital (RSJD) is the goal of this study. The basic data for this study came from a Likert scale questionnaire. There were 115 nurses in the research sample, and SPSS 29 software was utilized for the multiple linear regression analysis of the data. The study's findings provided evidence in favor of the premise that organizational commitment and workload significantly and negatively influence cyberloafing behavior. The recommendation for the Lampung Province Mental Hospital is to help create an atmosphere where nurses can feel content and at ease at work, as well as to inculcate positive values in them. The Lampung Provincial Mental Hospital ought to establish guidelines for the equitable distribution of nursing responsibilities. To lower the amount of cyberloafing among nurses, the Lampung Provincial Mental Hospital must also implement specific internet usage guidelines.